2006
DOI: 10.1074/jbc.m506403200
|View full text |Cite
|
Sign up to set email alerts
|

pH-dependent Equilibrium between Long Lived Near-UV Intermediates of Photoactive Yellow Protein

Abstract: Photoactive yellow protein (PYP) 3 (1) is a water-soluble photoreceptor protein suggested to be involved in the negative phototaxis of Halorhodospira halophila (2). PYP is an attractive model protein for a common signaling mechanism because it is a structural prototype of the PAS domain superfamily, most of which are involved in the biological sensing (3). PYP is composed of 125 amino acid residues and the p-coumaric acid chromophore linking to the cysteine residue by a thioester bond (4 -6). In the dark state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
66
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(70 citation statements)
references
References 41 publications
(79 reference statements)
4
66
0
Order By: Relevance
“…5). Basically, these results confirm previous work (18,25). At low pH pB has an absorption maximum of 368 nm, at medium pH an absorption maximum of 355 nm, and at high pH an absorption maximum of 430 nm, with corresponding pK a values at 5.9 and 9.9, respectively.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…5). Basically, these results confirm previous work (18,25). At low pH pB has an absorption maximum of 368 nm, at medium pH an absorption maximum of 355 nm, and at high pH an absorption maximum of 430 nm, with corresponding pK a values at 5.9 and 9.9, respectively.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, the pB intermediate has been shown to have absorption characteristics that depend on conditions such as pH, to the extent that it can be highly similar to pBЈ. Based on available infrared difference spectra of both pBЈ (17) and a pB intermediate with UV/visible absorption characteristics similar to pBЈ (18), we conclude that pBЈ and this pB are distinct intermediates. In this study, we will assume a unidirectional reaction between pBЈ and pB.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 A wide range of techniques have demonstrated that the formation of the signalling state of PYP is accompanied by large structural changes that lead to partial unfolding of the protein. 20,23,24,[27][28][29][30][31][32][33] These large structural changes are initiated by intra-molecular proton transfer and presumably assist in altering interactions with a downstream transducer.…”
Section: Introductionmentioning
confidence: 99%
“…The signalling state of PYP exists in multiple subspecies of which the degree of population depends on pH. 31 At pH 8 a 'medium pH' pB sub-species is dominant, while at pH 6 also a significant amount of the 'low-pH' pB species ( pK 5.9) is present. 52 The 'low pH' pB sub-species presumably is unfolded to a smaller extent than the 'medium pH' pB sub-species.…”
mentioning
confidence: 99%